Implementation Of Docker Container On Local Network By Applying Reverse Proxy - Henni Endah Wahanani; Mohammad Idhom; Kiki Yuniar Kristiawan (IJCONSIST JOURNALS, 2021)
Virtualization is an implementation of a software. Virtualization technology has changed the direction of the computer industrial revolution by reducing capital costs and operating costs. The availability of a virtualization will also increase the availability of higher services and data protection mechanisms. Docker is configured to create multiple containers on a network, each container containing one image. The three containers will be created in one compose where each container is connected to each other for WordPress configuration and two composers will be created. Furthermore, from each compose a reverse proxy configuration is carried out which aims to set a different domain address. Lighten computer performance and can reduce the required storage so as to make hosting more effective and efficient. Containers also provide a security advantage over complete control over management running on separate, isolated containers.